Ensuring sustainable energy supply of the Republic of Crimea with the help of public private partnership mechanisms - A. O. Sumenkov; M. V. Bogdanova; O. V. Baikova (Вестник университета)
The assessment of the current state of energy supply in the Republic of Crimea has been made. The main problems, that impede the successful gasification of the republic, such as the lack of funding, insufficient development of the institutional environment, weak human resources, and sanctions, - have been considered. The possible solutions to the problem of energy supply through public-private partnership mechanisms, in particular, a concession agreement have been suggested. Also the assessment of potential of the peninsula in the implementation of projects on the basis of a concession agreement has been made.